NASIONALISME DI INDONESIA - Afandi; Delvia Uliyanda; Fannisa Safarini; Ineke Laili Ramadhini; Ita Rahmadia; Jagad Aditya Dewantara; Sinta putri (Yayasan Nusantara Hasana Berdikari, 2023)
This study discusses the development of nationalism in a historical context, focusing on how the idea of ​​nationalism emerged, developed, and had an impact on society. The main objective of this study is to describe the development of nationalism from the past to the present. The research method used is a literature study. Research is conducted by reading journals, books or other sources related to nationalism in Indonesia. This literature study was conducted to understand more deeply about nationalism in Indonesia. The results of this research are expected to provide a better understanding of how nationalism develops and influences the development of society and the state. The implications of this research can provide insights for policy makers in formulating strategies that promote national unity, social integration, and sustainable development.